2022
DOI: 10.1155/2022/4561404
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Strength Quality of the Oryctolagus cuniculus Leather Compared to Oreochromis niloticus Leather

Abstract: This study aimed to compare the resistance of the Oryctolagus cuniculus L. (rabbit) and Oreochromis niloticus L. (Nile tilapia) skins, as well as to observe the design of the flower of these skins and the morphology of the dermis. Tilapia and rabbit skins were placed inside the same equipment (tannery machine) for the chromium salt tanning process. The flower design of the fish leather distinguishes it from the rabbit leather, the latter being constituted by the opening of the hair follicles and pores, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…For leather traction, despite the diagonal direction shown less resistance, the average value of leather traction was 12.29 N mm -2 . These resistance values are much lower than those of other leathers reported by Oliveira et al 27 Despite the greater thickness of paiche leather, Nile tilapia (22.17 N mm -2 ), cachara Pseudoplatystoma fasciatum (21.04 N mm -2 ) and salmon (18.21 N mm -2 ) leathers were more strength, and these leathers were 80.39, 71.20 and 48.17%, respectively, more strength than paiche leather.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…For leather traction, despite the diagonal direction shown less resistance, the average value of leather traction was 12.29 N mm -2 . These resistance values are much lower than those of other leathers reported by Oliveira et al 27 Despite the greater thickness of paiche leather, Nile tilapia (22.17 N mm -2 ), cachara Pseudoplatystoma fasciatum (21.04 N mm -2 ) and salmon (18.21 N mm -2 ) leathers were more strength, and these leathers were 80.39, 71.20 and 48.17%, respectively, more strength than paiche leather.…”
Section: Resultsmentioning
confidence: 53%
“…Concerning leather elasticity, despite paiche leather shown greater elasticity in the transverse direction (86.20%), the average leather elasticity was 68.81%, a value higher than those reported by Matiucci et al, 58 for Nile tilapia (52.63%), pacu (72.50%) and tambaqui (66.69%) leathers, which was the closest to average elasticity value of paiche leather. However, leathers with greater elasticity were observed by Oliveira et al 27 These authors reported that Nile tilapia (108.43%) and salmon (111.00%) leathers showed a high elongation value resulting from action of fatliquoring, providing greater resistance and elongation (elasticity) in the leather, improving characteristics physicomechanical properties of this leather. In research by Franco et al 59 and Oliveira et al 27 the ratio of oil used by leather thickness was 9.33, while in this study with paiche, despite a higher percentage of oil used in the fatliquoring stage, when observed the ratio with leather thickness was much lower (4/13).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations